Utilizing AEOLUS to Improve Dust Transport Modelling - Thanasis Georgiou; Konstantinos Rizos; Athanasios Tsikerdekis; Emmanouil Proestakis; Antonis Gkikas; Holger Baars; Athena Augusta Floutsi; Eleni Drakaki; Anna Kampouri; Eleni Marinou; Dave Donovan; Angela Benedetti; et al. (Environmental Sciences Proceedings, 2023)
The European Space Agency’s AEOLUS mission provides vertical profiles of the horizontal line-of-sight (HLOS) wind component in the troposphere and lower stratosphere, as well as secondary products with retrievals of extinction and backscatter coefficients. Under the scope of the ESA L2A+ project, we present an assimilation system of both wind and aerosol information from AEOLUS in a regional numerical weather prediction model (WRF). This study aims to highlight the impact of such a dataset on desert dust transport through assimilation experiments over the broader North Atlantic Ocean region, which features high dust transport events through the Saharan Air Layer. The results will be validated through comparisons with observations from the ESA-ASKOS/JATAC experiments.